Knowledge Management Technologies for Collaborative Intelligence: A Study of Case Company in Korea - Kyung Jin Cha; Yang Sok Kim; Byeonghwa Park; Choong Kwon Lee (International Journal of Distributed Sensor Networks)
To create wide and deep knowledge flows by providing implicit and explicit knowledge services, organizations have constructed knowledge management systems (KMS). As employees are major knowledge resources in an organization, it is essential to use their collaborative intelligence in KMS, but there has been little research on how the heterogeneous networks of people interact to produce intelligent outcomes. This research suggests a new KM framework that leverages collaborative intelligence techniques, such as collaborative search, collaborative filtering, and social network analysis, as well as conventional knowledge management techniques including smart sensor technology. Finally, this paper reports our experience in a real world KMS development case that applied the framework and suggests challenges of knowledge management learned from this research.